External auditors' trust and perceived quality of interactions - Kwok Yip Cheung; Chung Yee Lai (Cogent Business & Management, 2022)
The external auditor cooperates and communicates with the audit committee of a company to ensure effective external audit, including detection of material misstatements in financial statements. Trust is an important element to facilitate information exchange and cooperation. This exploratory research examines the impacts of external auditors' trust in audit committee members' competence, integrity and goodwill on perceived quality of their interactions. Through questionnaire survey, the data were collected from audit managers, senior managers, directors and partners in Hong Kong with a response rate of 27.2 percent. Partial least square structural equation modeling and principal component analysis were employed to test the proposed model. The results reveal that the external auditor's competence trust and integrity trust in the audit committee members are two strong motivators, which improve their interactions with the audit committee. The findings also confirm that perceived quality of interactions during pre-engagement investigation mediates the impacts of competence trust and integrity trust on perceived quality during audit performance stage. The implication of the study is that audit committee members should display high levels of competence and integrity for better interactions with external auditors. These findings provide inspirations for board of directors, executives and policymakers to implement policies that enhance trust among actors to improve audit quality.
Keywords: 650; Audit quality; Competence trust; Goodwill trust; integrity trust; perceived quality of interactions